VITALITAS BAHASA SUNDA DI KABUPATEN KUNINGAN (SUNDANESE VITALITY IN KUNINGAN REGENCY ) - Ariyanti Ariyanti; Ayi Sofyan (Balai Bahasa Jawa Barat, 2021)
Language vitality study is a study conducted to measure the vitality of a language. According to Harimansyah (2020), the vitality of a language refers to the intensity of using, existence, and language inheritance as a means of communication in various social contexts. Sundanese is one of the languages that has been identified in the Language and Language Map in Indonesia (2019) and has a large number of speakers. However, this does not mean that Sundanese is safe. Kuningan Regency was chosen as the research location because the population speaks Sundanese and is located close to Central Java. Therefore, it is necessary to study whether Sundanese is still spoken by the people of Kuningan Regency, is Sundanese in Kuningan Regency included in the group of languages that have experienced decline, and should Sundanese language in Kuningan Regency be conserved or revitalized? In order to reveal these problems, the data obtained through questionnaires were analyzed using quantitative methods. The results showed that the proportion of people in Kuningan Regency who still spoke Sundanese was 82%, Sundanese in Kuningan Regency was not included in the language group that was eroding, but included the language vitality that was stable but threatened, and Sundanese in the language. Kuningan Regency does not have to be conserved or revitalized because it is still considered stable but threatened.